THE USE OF THE INVERTED CLASSROOM ACTIVE METHODOLOGY IN TEACHER TRAINING IN PANDEMIC TIMES - SILVA, LUCAS FERREIRA (2022)
This work is an experience report of the application of a training course for teachers with active methodologies, remotely, with the purpose of providing students with training to work with active methodologies. It is also investigated remnants of mechanized learning, at this time of a pandemic, however, it is necessary to prepare another article to analyze the data, not fitting in this work to expose this quantification, but to report the experience of it. With this, the theoretical foundation denounces the traditional practices that still permeate teaching today, justifying the need to train teachers to provide an active and meaningful learning experience. For the implementation of the course, Google Classroom was used together with the Inverted Classroom. This platform enabled the collection of research data as well as favoring the organization of the virtual environment. It is concluded that the production of pedagogical materials to assist and guide through active methodologies is of great importance, since most of the works are in normal moments and not exceptional ones like the one now.